Dynamics and diversity of microbial community succession during fermentation of Suan yu, a Chinese traditional fermented fish, determined by high throughput sequencing. (September 2018) - Zang, Jinhong; Xu, Yanshun; Xia, Wenshui; Yu, Dawei; Gao, Pei; Jiang, Qixing; Yang, Fang
Abstract: The main goal of this study was to investigate the dynamics, diversity and succession of microbial community present during the preparation of Suan yu (fermented fish), with and without starter cultures by high-throughput sequencing of 16S rRNA and ITS1 genes. Firmicutes and Ascomycota were the predominant phyla of bacteria and fungi, respectively, in all samples. At the genus level, Lactobacillus, Macrococcus and Staphylococcus were the predominating bacteria throughout the fermentation process, regardless of the inclusion of starter cultures. Saccharomyces was the predominating fungal genus in the early-fermentation stage of samples that inoculated starter cultures (MS), while the final product was dominated by Candida and Wickerhamomyces . Compared with naturally-fermented samples (NS; no starter cultures), Lactococcus, Leuconostoc, Enterococcus, Vibrio, Fusicolla and Torulaspora were inhibited and Aureobasidium emerged in samples inoculated with starter cultures ( P  < .05). Unweighted pair-group and principal component analyses of bacterial and fungal compositions revealed that microbiota structures differed between NS and MS samples. Redundancy analysis indicated that water content and pH might be important factors influencing the dominant bacterial and fungal community. Results indicated that microbial community were dynamic during fermentation process and the inoculation of mixed starter culture inhibited the growth of many organisms associated with food spoilage and contributed to the improvement of the quality of Suan yu products. Graphical abstract: Unlabelled Image Highlights: High-throughput sequencing was firstly applied in Suan yu fermentation. Major microbial community in different fermentation stages was identified. The fungal diversity was greater than that of the bacterial in fermentation process. The effect of starter cultures on microbial community dynamics was investigated. Water content and pH exert significant effects on the change of dominating microbes